(untitled) (Revista Cientifica Ingenio Magno, 2022)
Abstract— In the development of new sustainable technologies, the production of biomass through the whey obtained in the transformation of dairy derivatives as raw material, is presented as a low-cost alternative. In the article, a detailed bibliographic review is developed, from the whey production process to the proposal for the implementation of a useful thermal and electrical energy cogeneration system. In the first section of the document, the reader is introduced to the biochemical and industrial process of treatment of dairy products, in the intermediate sections the process of generating electric current is described through the proposal based on the research project PS362020-2 of the University Nacional Abierta y a Distancia - UNAD in alliance with the Mayor’s Office of the municipality of Sopó in Cundinamarca, where a vision of the expected environmental impact is proposed in the case of using whey as raw material. Finally, in the discussion and conclusions, the process is mentioned as an alternative for the generation of viable and resilient energy, capable of opening a market around sustainable use in the dairy sector.